2020
DOI: 10.1109/jeds.2020.2970177
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Extraction and Compact Modeling of 1/f Noise for Amorphous ESL IGZO TFTs

Abstract: In this paper, the flicker noise properties of bottom-gate ESL structured amorphous InGaZnO (a-IGZO) thin-film transistors (TFTs) from two different technologies have been studied and modeled. Model development is carried out by adapting the Unified Model parameter Extraction Method (UMEM), developed for parameter extraction and compact modeling of TFT devices, and the unified 1/f noise model. Furthermore, comparative study of device figures of merits is performed to point out the device performance enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Furthermore, physical models of leakage current, subthreshold characteristics, contact resistance, short channel effects, frequency dispersion, aging, and process variations are of great potential to be improved for model accuracy and universality for different technologies (figure 26). Low frequency noise modelling is also important for flexible TFTs to be used in low power analogue design [134]. Depending on the TFT technologies, the low frequency noise could be dominated by either carrier number fluctuation or mobility fluctuation.…”
Section: Advances In Compact Modelling To Meet Challengesmentioning
confidence: 99%
“…Furthermore, physical models of leakage current, subthreshold characteristics, contact resistance, short channel effects, frequency dispersion, aging, and process variations are of great potential to be improved for model accuracy and universality for different technologies (figure 26). Low frequency noise modelling is also important for flexible TFTs to be used in low power analogue design [134]. Depending on the TFT technologies, the low frequency noise could be dominated by either carrier number fluctuation or mobility fluctuation.…”
Section: Advances In Compact Modelling To Meet Challengesmentioning
confidence: 99%
“…Comparison of the carrier number fluctuation, mobility fluctuation and unified models in linear regime. In the devices targeted the normalized drain current spectral density was inversely proportional to the channel length, what indicated that the Flicker noise was mostly generated in the channel and not in the contacts [96][97][98]. To determine the dominant noise mechanism, I-V measurements were carried out in order to extract model parameters.…”
Section: Temperature Effectsmentioning
confidence: 99%
“…Afterwards, a full compact model for the Flicker noise in IGZO TFT was developed and successfully compared with experimental data [97] (Fig. 29).…”
Section: Temperature Effectsmentioning
confidence: 99%